2020
DOI: 10.1038/s41467-019-14258-z
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid differentiation regulator-1 induced by microbiota in early life drives intestinal stem cell proliferation and regeneration

Abstract: Gut microbiota and their metabolites are instrumental in regulating intestinal homeostasis. However, early-life microbiota associated influences on intestinal development remain incompletely understood. Here we demonstrate that co-housing of germ-free (GF) mice with specific-pathogen free (SPF) mice at weaning (exGF) results in altered intestinal gene expression. Our results reveal that one highly differentially expressed gene, erythroid differentiation regulator-1 (Erdr1), is induced during development in SPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…It is also crucial to fully characterize the status of animals from which IESC are isolated to produced intestinal organoids (e.g. developmental stage, diet, gut microbiota, infectious status) since IESC imprinting in vivo might impact long term epithelial phenotype in organoids in vitro [ 57 , 58 ]. However, human studies showed that traces of epigenetic regulation in intestinal organoids (related for example to effects of microbiota or chronic disease condition) were progressively erased during cell culture passaging for amplification [ 59 ].…”
Section: Future Directions Of Research With Livestock Intestinal Orgamentioning
confidence: 99%
“…It is also crucial to fully characterize the status of animals from which IESC are isolated to produced intestinal organoids (e.g. developmental stage, diet, gut microbiota, infectious status) since IESC imprinting in vivo might impact long term epithelial phenotype in organoids in vitro [ 57 , 58 ]. However, human studies showed that traces of epigenetic regulation in intestinal organoids (related for example to effects of microbiota or chronic disease condition) were progressively erased during cell culture passaging for amplification [ 59 ].…”
Section: Future Directions Of Research With Livestock Intestinal Orgamentioning
confidence: 99%
“…Apart from microbial sensing, the microbiota shapes the functionality and performance of the intestinal epithelial stem cell niche during development. Bacterial exposure at weaning affected gene expression of the erythroid differentiation regulator-1 ( Erdr1 ), which is important for stem cell proliferation and regeneration after epithelial damage in the neonatal colon ( 159 ). However, already before weaning, microbial metabolites influence intestinal epithelial renewal.…”
Section: Gastrointestinal Epithelial Barrier and Gut Commensals Early In Lifementioning
confidence: 99%
“…In healthy subjects, the gut microbiota is in homeostasis. The alteration of intestinal microbiota is reported to be linked to the development of inflammation present in different pathological conditions such as chronic intestinal disease, inflammatory bowel disease, asthma, diabetes mellitus, and metabolic syndrome [ 147 , 148 , 149 , 150 , 151 , 152 ]. The dysregulation in nutrient absorption and metabolism has been associated to obesity [ 153 , 154 ].…”
Section: Th17 and Treg Dysregulation In Obesity-induced Inflammationmentioning
confidence: 99%